PENGARUH MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) BERSETTING PROBLEM POSSING TERHADAP HASIL BELAJAR SISWA POKOK BAHASAN STOIKIOMETRI KELAS X IPA SMA NEGERI 8 PONTIANAK - Fitriani Fitriani; Tuti Kurniati; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACT This study aimed at finding out the difference, the influence, and the implementation of students’ learning outcomes on Stoichiometry taught by using problem posing and lecturing method of Numbered Heads Together (NHT) cooperative model in class X, SMA 8 Pontianak. Using quasi experimental and Nonequivalent Control Group designs, this study employed students of class X MIA 1 as the experimental group and class X MIA 4 as the control group. The study revealed that the average score of experimental class was higher (78,06) than the control class (67,30). The affective assessment of the control class gained lower score than the experimental class with the Excellent criteria at the first and the second meeting. Whereas, the affective assessment for Good criteria was dominated by the control class with the average score of 78,26%. The results of Uman witney test (α=0,05) showed that significance score of 0,000 which means that there was significant difference of control and experiment classes. The effect size calculations indicated ES=0.57 which categorized into average. Therefore, problem posing and lecturing method of Numbered Heads Together (NHT) cooperative model contributed positive influence to the students’ learning outcomes (21,57).Keywords : Students’ Outcomes, Numbered Heads Together (NHT), Problem Possing